Experimental implementation of a linear control technique for a single-phase matrix converter - Rivera, Marco; Rojas, S.; Wheeler, Patrick; Yaramasu, V. (2016)
This paper describes a matrix converter with a three-phase input and single-phase output that can be used as a building block for high-power cascaded converters. In this paper a sinusoidal pulse width modulation technique with a linear controller is proposed for the single-phase output matrix con¬verter. The proposed modulation and control will be used in the cascade configurations for high-power applications. Simulation and experimental results are presented to validate the proposed modulation and control approach.